Fruit and Vegetable consumption and overweight among School age children within the "COSI" portuguese study - Rito, Ana (2011)
A full list of all Portuguese private and public primary schools (N=6810) was provided by the Ministry of Education. A simple random two-stage sampling was applied and a nationally representative sample was drawn, with schools as the first unit of sampling. 189 schools were selected. Data from first and second graders(6A8 years old) from 181 primary schools of the seven geographical regions of Portugal (North, Centre, Lisbon and Tagus Valley, Alentejo, Algarve, Azores and Madeira) were collected.